2015
DOI: 10.1080/15384047.2015.1046021
|View full text |Cite
|
Sign up to set email alerts
|

miRNA profiling in vitreous humor, vitreal exosomes and serum from uveal melanoma patients: Pathological and diagnostic implications

Abstract: Uveal melanoma (UM) represents approximately 5-6% of all melanoma diagnoses and up to 50% of patients succumb to their disease. Although several methods are available, accurate diagnosis is not always easily feasible because of potential accidents (e.g., intraocular hemorrhage). Based on the assumption that the profile of circulating miRNAs is often altered in human cancers, we verified whether UM patients showed different vitreous humor (VH) or serum miRNA profiles with respect to healthy controls. By using T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(156 citation statements)
references
References 46 publications
7
148
0
1
Order By: Relevance
“…We used miR-320a as reference gene for normalization of human serum samples (Ragusa et al, 2015), U6 and miR-16 for rat serum and retina samples (Tea et al, 2013). Real Time PCRs was carried out on a 7,900 HT Fast Real Time PCR System (Applied Biosystems, Monza, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…We used miR-320a as reference gene for normalization of human serum samples (Ragusa et al, 2015), U6 and miR-16 for rat serum and retina samples (Tea et al, 2013). Real Time PCRs was carried out on a 7,900 HT Fast Real Time PCR System (Applied Biosystems, Monza, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, miR-155 has been shown to promote the expansion of pathogenic Th17 cells, which mediate experimental uveitis 41 ; intravitreal miR-21 and miR-146 have been demonstrated as tumor markers of uveal melanoma 26 ; and intravitreal miR-146 has been demonstrated to control retinal inflammation in diabetic retinitis. 23 Further, the expression levels of microRNA transcripts have been compared between patients with proliferative diabetic retinopathy and patients with MH.…”
Section: Discussionmentioning
confidence: 99%
“…In group 3, four blood serum samples were collected in addition to SRF from the same patients (Nos. [26][27][28][29].…”
Section: Patientsmentioning
confidence: 99%
“…A study by Ragusa et al revealed that exosomes derived from uveal melanoma patients contained a common miRNA in the exosomes, miR-146a, within the vitreous humor, as well as those circulating through the body [93]. Another miRNA in exosomes, miR-126b, was down-regulated only in patients with advanced melanoma compared to healthy donors [94].…”
Section: Exosomes and Melanomamentioning
confidence: 99%